Unique f ( x ) f\left( x \right)

Algebra Level 4

A real valued function satisfies the following conditions:

(1) f ( x 1 ) + f ( x + 1 ) = 2 f ( x ) f \left( x-1 \right) +f \left( x+1 \right) = \sqrt{ 2 } f \left( x \right) for x < 1 x < -1 or x > 7 x > 7 .
(2) f ( x ) = x for 0 x 7. f\left( x \right) =x \mbox{ for } 0\le x\le 7.

Find the value of f ( 87 ) f(87) .


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Harsh Depal
Mar 24, 2014

f ( x ) = 7 f(x)=7
But For x > 7 x>7 ,
f ( x 1 ) + f ( x + 1 ) = 2 f ( x ) . . . . . . . . . . . . . . . . . ( 1 ) f(x-1)+f(x+1)=\sqrt { 2 } f(x).................(1)

Multiplying Equation 1 With 2 \sqrt { 2 } ,
2 f ( x 1 ) + 2 f ( x + 1 ) = 2 f ( x ) . . . . . . . . ( 2 ) \sqrt { 2 } f(x-1)+\sqrt { 2 } f(x+1)=2f(x)........(2) .

Replacing x x by x 1 x-1 in Equation 1,
f ( x 2 ) + f ( x ) = 2 f ( x 1 ) . . . . . . . . . . . . . . . . . . ( 3 ) f(x-2)+f(x)=\sqrt { 2 } f(x-1)..................(3)

Replacing x x by x + 1 x+1 in Equation 1,
f ( x + 2 ) + f ( x ) = 2 f ( x + 1 ) . . . . . . . . . . . . . . . . . ( 4 ) f(x+2)+f(x)=\sqrt { 2 } f(x+1).................(4)

Adding Equations (2),(3) and, we Get
f ( x 2 ) + f ( x + 2 ) = 0............................... ( 5 ) f(x-2)+f(x+2)=0...............................(5)

Replacing x x by x + 4 x+4 in (5), we get
f ( x + 2 ) + f ( x + 6 ) = 0................................ ( 6 ) f(x+2)+f(x+6)=0................................(6)

Therefore, equating equation (5) and (6),

f ( x 2 ) = f ( x + 6 ) f(x-2)=f(x+6) and therefore f ( x ) = f ( x + 8 ) f(x)=f(x+8)

So f ( 7 ) = f ( 15 ) = f ( 23 ) = f ( 87 ) f(7)=f(15)=f(23)=f(87) Hence f ( 87 ) = 7 f(87)=\boxed { 7 } .

Nice! :)

Happy Melodies - 7 years, 2 months ago

your solution is beautiful

Romeo Gomez - 6 years, 10 months ago

Very good job. Congratulations.

Niranjan Khanderia - 6 years, 10 months ago
Mas Mus
Apr 11, 2014

by equation (2) we get f(6) = 6 and f(7) = 7. Substitution f(6) and f(7) to equation (1) to get f(8). Based on equation (1), compute f(9), f(10), and so on. we will have an unique pattern f(7) = f(15) = f(23) = f (31) = ... = f(87) = 7

Anirudha Nayak
Mar 24, 2014

Manipulate to find the period of function to be T=8

f(87)=f(7)=7 (from equation(2))

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...